Sensitivity of Meloidogyne incognita and Rotylenchulus reniformis to Cyclobutrifluram - Brown, Katherine (Plant disease, 2024)
Cyclobutrifluram, a succinate dehydrogenase inhibitor fungicide, is being evaluated as a seed-applied nematicide in cotton and soybean to manage plant-parasitic nematodes. Currently, there is no information on the toxicity, ovicidal activity, nematode recovery, or effects on nematode infection for Meloidogyne incognita or Rotylenchulus reniformis after exposure to low concentrations of cyclobutrifluram. Nematode toxicity assays were performed in aqueous solutions of cyclobutrifluram, and root infection assays were conducted on tomato. Nematode paralysis was observed after 2 h of exposure to 0.5 μg/ml cyclobutrifluram for both nematode species. Based on an assay of nematode motility, the 2-h effective concentration of fungicide required for 50% growth inhibition (EC50) value for M. incognita and R. reniformis was 0.48 and 1.07 μg/ml, respectively. In a comparable assay with a similar nematicide, continuous exposure to 0.5 μg/ml cyclobutrifluram for 24 h resulted in at least 45% more immotile nematodes for both species compared with those treated with 0.5 μg/ml fluopyram. Continuous exposure to concentrations greater than 1.0 μg/ml suppressed hatching for both species compared with the water control. Nematode recovery from paralysis was greater than 80% for M. incognita and R. reniformis 24 h after nematodes were rinsed and removed from a 1-h treatment to their respective 2-h EC50 concentrations. Nematode infection of tomato roots was reduced following a 1-h treatment with aqueous solutions of cyclobutrifluram, ranging from 0.12 to 0.48 μg/ml for M. incognita and 0.27 to 1.07 μg/ml for R. reniformis. Overall, the toxicity of cyclobutrifluram to these nematode species was greater than that of fluopyram, and although the effects of cyclobutrifluram were reversible, low concentrations were effective at reducing the ability of both nematodes to infect tomato roots